Cerebral Microstructural Alterations after Radiation Therapy in High-Grade Glioma: A Diffusion Tensor Imaging-Based Study - Kassubek, Rebecca; Gorges, Martin; Westhoff, Mike-Andrew; Ludolph, Albert C.; Kassubek, Jan; Müller, Hans-Peter (Frontiers in Neurology, 2017)
Objective: To investigate radiation therapy-induced microstructural damage of white matter in patients with high-grade glioma by diffusion tensor imaging (DTI). Methods: DTI was performed in eighteen patients with high-grade glioma (WHO grades III and IV) and thirteen healthy controls. DTI images were cross-sectionally aligned for the calculation of baseline fractional anisotropy (FA). Interhemispheric FA values in patients with high-grade glioma before or without brain radiation therapy were compared with the interhemispheric FA values in patients after radiation therapy and in healthy controls. In a subgroup without any clinical or diagnostic evidence of tumour progression, serial DTI data (5 – 11 scans) before and after radiation therapy were collected and longitudinal interhemispheric FA changes were assessed, and compared to longitudinal data from the control group. In addition, interhemispheric axial, mean, and radial diffusivity was assessed. Results: Global interhemispheric FA reductions could be detected cross-sectionally in patients after radiation therapy; these were significantly different from global interhemispheric FA differences, both in patients without radiation and in healthy controls. Longitudinal scans in the patients with radiation therapy confirmed these findings and revealed progressive microstructural white matter damage after partial brain radiotherapy. The additional DTI metrics AD, MD and RD confirmed interhemispheric differences for patients without or before radiation therapy that were lower than the differences for patients after radiation therapy, however, not reaching significance. Conclusion: Interhemispheric global FA differences could potentially serve as a biological marker for irradiation-induced microstructural white matter damage.